2019
DOI: 10.1177/1748895819839751
|View full text |Cite
|
Sign up to set email alerts
|

Achieving cultural change through organizational justice: The case of stop and search in Scotland

Abstract: In recent years, the scale, impact and legality of stop and search in Scotland has been subject to intense critical scrutiny, leading to major legal and policy reform in 2016. Based on these events, including an early unsuccessful attempt by Police Scotland to reform the tactic (the 'Fife Pilot'), this paper presents original theoretical and empirical insights into organizational change in policing. Building on the theoretical perspectives of Chan (1997) and Bradford and Quinton (2014) on organizational cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…During the intervisions, the impact of organisational justice on procedural justice became more central (in the same sense: Aston et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the intervisions, the impact of organisational justice on procedural justice became more central (in the same sense: Aston et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the tool can help to increase communication between different levels on the content of patrolling, which in turn has an influence on organisational justice. Scholars recently concluded that emphasising organisational justice can lead to cultural change (Aston et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campeau (2019) refers to these as formal and informal myths of police agencies, while others have referred to these as the working rules of police culture (Stroshine et al, 2008). This perspective does not view police culture as a static, linear, or monolithic, but rather as a culture that is routinely shaped by the various conditions present in policing (Aston et al, 2019). These myths or working rules may be influenced by generational differences between officers which can create "old" and "new" cultural scripts (Campeau, 2019), adopted by officers relating to shifting demographics and policy reforms, or through officers work environments (Campeau, 2018;Carlson, 2019).…”
Section: Police Culturementioning
confidence: 99%
“…Bellingham (2000, p. 37) argues that "formal rules must be tightened since it is the permissiveness of these rules that creates the space for occupational culture to flourish and foster its resistance to change." In some instances, officers may understand the need for change and what they are being asked to do, but when it is perceived as being imposed by senior management or enforced from outside of the police agency, then change is unlikely to be viewed as fair and officers will often struggle with adopting the practice in any meaningful way (Aston et al, 2019). By failing to change the police culture to adapt to new policy initiatives, officers can perceive new initiatives as a "self-inflicted bureaucratic burden" (Aston et al, 2019, p. 11).…”
Section: Issues With Policy Implementationmentioning
confidence: 99%